Ultra-low contrast coronary angiography and zero-contrast percutaneous coronary intervention for prevention of contrast-induced nephropathy: step-by-step approach and review - Sacha, Jerzy; Gierlotka, Marek; Feusette, Piotr; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2019)
Contrast-induced nephropathy is a serious complication after intravascular administration of iodinated contrast media and is associated with numerous adverse outcomes. Its prevalence is particularly high in patients with multiple comorbidities who undergo coronary angiography and percutaneous coronary intervention (PCI). Currently, the only effective method to prevent contrast-induced kidney injury is adequate hydration and a reduction of contrast volume during the intervention. Recently, new approaches aiming to minimize contrast usage have been proposed, i.e., ultra-low contrast angiography and zero-contrast PCI. However, neither tutorials for these techniques nor reviews of their outcomes exist in the literature, and therefore dissemination of these approaches among the interventional community may be limited. This article presents a step-by-step description on how to perform ultra-low coronary angiography and zero-contrast PCI, which should help invasive cardiologists to adopt these techniques in daily practice. A review of clinical studies, case series and single case reports regarding these methods is also provided. Despite the promising results, such procedures still require some improvements and confirmation of their effectiveness as well as safety in large clinical studies. This article aims to spread these new techniques throughout the interventional community, which is paramount for their further development and wider utilization.